THE APPLICATION OF THE TEAM ASSISTED INDIVIDUALIZATION (TAI) TYPE OF COOPERATIVE MODEL IN THE STUDENTS' IPA LEARNING IN CLASS V SD NEGERI 49 LUBUKLINGGAU - Nurhudha, Nurhudha; Lokaria, Eka; Asmara, Yeni (Universitas Trunojoyo Madura, 2022)
This research by Nurhudha NPM 5018077 entitled the application of the Team Assisted Individualization (TAI) type cooperative learning model in science learning for fifth grade students of SD Negeri 49 Lubuklinggau with the main supervisor Yeni Asmara, M.pd and the assistant supervisor Eka Lokaria, M.pd, Si. The purpose of this study was to determine the completeness of science learning outcomes for fifth grade students of SD Negeri 49 Lubuklinggau after the cooperative model of Team Assisted Individualization (TAI) was applied. This type of research is a pre-experimental design research that was carried out without a comparison class with a pre-test and post-test group design. The population is the entire fifth grade of SD Negeri 49 Lubuklinggau for the academic year 2021/2022, which consists of 47 students consisting of two classes and as the sample is class V.A which is taken at random by 23 students. data collection was taken by test technique. The collected data were analyzed using t-test. based on the results of the t-test analysis at a significant level = 0.05, obtained t_count (20.11) t_table (1.717), so it can be concluded that the learning outcomes of science learning for fifth graders at SD Negeri 49 Lubuklinggau after the implementation of the Team Assisted Individualization cooperative model (TAI) significantly completed.